ANALISIS PENGARUH ANTISIPASI NILAI PELANGGAN DAN KOMUNIKASI PEMASARAN TERHADAP MINAT MENGADOPSI (Studi Pada Produk Telkom Indihome Triple Play Semarang) - Hapsari, Yunita Chandra; Sukresna, I Made (Diponegoro Journal of Management, 2017)
In this modern era, the need for technology, information and communication is growing rapidly. As the need grow greater, service providers are required to present a service that can follow the development of technology but in accordance with the needs and accepted by the society. Telecomunication and Network companies in Indonesia offerÂ  many attractive products and with various benefits as a form of competition. As one of telekomunication company in indonesia, PT. Telekomunikasi Indonesia Tbk (Persero) or Telkom, presents their innovative product called Indihome Triple Play. This product combine three services in one product, thatÂ  consist of High Speed Internet on Fiber, Phone, dan Interactive TV. This research aimed to analyze the effect of Customer Value Anticipation and Marketing Communication on Intention to Adopt.The sample in this study is 130 respondents of Indihome Triple Play customers, using the method of Structural Equation Modeling (SEM) The results of this study indicate that Customer Value Anticipation and Marketing Communication have positive and significant influence on Product Innovativeness (as intervening variable), and Product Innovativeness has positive and significant effect on Intention to Adopt.